2022
DOI: 10.3390/toxins14090641
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Protects against Zearalenone-Induced Mitochondrial Defects during Porcine Oocyte Maturation via PINK1/Parkin-Mediated Mitophagy

Abstract: Mitochondria hold redox homeostasis and energy metabolism as a crucial factor during oocyte maturation, while the exposure of estrogenic mycotoxin zearalenone causes developmental incapacity in porcine oocyte. This study aimed to reveal a potential resistance of phytoalexin resveratrol against zearalenone during porcine oocyte maturation and whether its mechanism was related with PTEN-induced kinase 1 (PINK1)/Parkin-mediated mitophagy. Porcine oocytes were exposed to 20 μM zearalenone with or without 2 μM resv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Previous studies have shown that ZEN affects animal oocyte maturation mainly via the expression of genes involved in oocyte maturation, cumulus expansion factor, oxidative stress, cell apoptosis, autophagy, and spindle assembly checkpoint [9][10][11][12][13][14][15][16][17]. The overall transcriptome data analysis revealed that ZEN induced oxidative stress, promoted apoptosis and autophagy, and inhibited oocyte development and spindle assembly, thus impeding ovine oocyte IVM.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have shown that ZEN affects animal oocyte maturation mainly via the expression of genes involved in oocyte maturation, cumulus expansion factor, oxidative stress, cell apoptosis, autophagy, and spindle assembly checkpoint [9][10][11][12][13][14][15][16][17]. The overall transcriptome data analysis revealed that ZEN induced oxidative stress, promoted apoptosis and autophagy, and inhibited oocyte development and spindle assembly, thus impeding ovine oocyte IVM.…”
Section: Discussionmentioning
confidence: 94%
“…In pigs, ZEN can significantly increase the phosphatidylcholine or phosphatidylethanolamine content and consume hemolysin phosphatidylcholine, thereby impairing follicular cavity formation and oocyte maturation [11]. In mice and pigs, ZEN can increase oxidative stress and disrupt spindle assembly and chromosome separation, leading to premature condensation of chromatin and interfering with the expression of genes related to oocyte activity, spindle assembly, redox potential, and apoptosis, thereby inhibiting the discharge of polar bodies and cumulus expansion and affecting oocyte maturation [12,13]; it also causes autophagy, apoptosis, and oxidative stress and disrupts embryo development by affecting the expression of epigenetic histones and organelle structure and function (mitochondria, endoplasmic reticulum, Golgi apparatus, and lysosomes), in turn affecting oocyte maturation and ovarian follicle formation [14][15][16]. It has a damaging effect on preantral follicles in ovine ovaries and participates in oocyte autophagy, although the specific mechanism of toxicity is unknown [17].…”
Section: Introductionmentioning
confidence: 99%
“…ZEA is one of the most common mycotoxins. Numerous studies have shown that it affects the reproductive capacity of animals [ 25 , 26 , 27 ]. The widespread distribution of ZEA in animal feed exposes farm animals to its toxic effects, which is a global public health problem [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…CoQ10 significantly prevented aging-induced oxidative stress, and increased mitochondrial biogenesis (SIRT1 and PGC1α) and mitophagy (PINK1 and Parkin)-related proteins in postovulatory oocyte of pigs ( 104 ). Resveratrol can increase the expression of PINK1 and Parkin proteins regulate the autophagy ability of mitochondria, and protect ovarian function ( 175 ). Metformin and Melatonin are AMPK activators ( 105 , 174 ), which could increase intracellular calcium concentrations thereby increasing the induction of mitochondrial biogenesis through transcription factors (such as NRFs, TFAM) ( 111 ).…”
Section: Methods To Slow Down Ovarian Aging and Prolong Reproductive ...mentioning
confidence: 99%